Burden Sharing in CSDP Military Operations. Issue 7 (10th November 2018) - Haesebrouck, Tim; Thiem, Alrik
Abstract: Military burden sharing has been a subject of repeated debates in NATO and the UN. Despite more modest goals, the European Union's (EU) Common Security and Defense Policy (CSDP) has experienced no fewer difficulties in garnering men, money, and materiel. While this may not come as a surprise, the fact that some EU member states have carried disproportionate shares of the burden of CSDP operations is a puzzle that remains unaccounted for. We address this gap by analyzing determinants of contribution levels to CSDP operations. In employing an innovative multi-method design that combines insights from collection action theory with those from integrated theories of military burden sharing, our results indicate that EU countries tend to contribute in positive disproportion with their capabilities when they have a strong peacekeeping tradition and elections are distant. In contrast, they undercontribute when small trade volumes with the area of operations combine with a weak peacekeeping tradition.